1994
DOI: 10.1002/qua.560490406
|View full text |Cite
|
Sign up to set email alerts
|

Protonation of fused aromatic systems: Ab initio study of some model Wheland intermediates

Abstract: Structure and properties of Wheland's intermediates are studied in some model systems. The effect of the annelated small ring is simulated by bending two vicinal CH bonds in benzene toward each other. The extent of bending describes the ring-size effect of a small fused fragment molecule. The electrophilic substituent is represented by a proton. Calculations at the HF/6-31G* and MP2//HF/6-31G* levels of sophistication confirm the Mills-Nixon (MN) hypothesis. It is conclusively shown that P-complexes are more s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…A reason behind the more pronounced susceptibility toward the proton attack of position 1 relative to position 2 is very instructive. It is well-known that a substantial bond fixation takes place in benzenonium ion exhibiting a quite characteristic pattern, which is reflected inter alia in the corresponding L ( d ) index ( vide supra ). Careful examination of the B3-LYP/6-31G* and MP2(fc)/6-31G* geometries shows that a dominant mode of π-bond localization of the benzenonium ion is preserved to some extent in the protonated forms 1 1 and 1 2 leading to slightly predominant pairing schemes shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A reason behind the more pronounced susceptibility toward the proton attack of position 1 relative to position 2 is very instructive. It is well-known that a substantial bond fixation takes place in benzenonium ion exhibiting a quite characteristic pattern, which is reflected inter alia in the corresponding L ( d ) index ( vide supra ). Careful examination of the B3-LYP/6-31G* and MP2(fc)/6-31G* geometries shows that a dominant mode of π-bond localization of the benzenonium ion is preserved to some extent in the protonated forms 1 1 and 1 2 leading to slightly predominant pairing schemes shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Combination of these PA values with thermodynamic data measured in solution provides a valuable source of information on solvent effects thus enabling a clear-cut distinction to be made between intrinsic and external (intermolecular) interactions. Additionally, the proton is the simplest example of the electrophilic substituent group, which has proved very useful in developing a general picture of the electrophilic reactivity of aromatics, particularly in elucidating the effect of annealation of small strained rings. , We note in passing that the angular strain considerably affects basicity through rehybridization as confirmed by a meticulous theoretical analysis by Yáñez et al recently. Experimental determination of PAs encounters some difficulties since they are estimated usually by measuring gas-phase equilibrium constants for reactions implying that, strictly speaking, only the relative values for bases B 1 and B 2 could be obtained. , Choice of different anchor (gauge) base(s) leads to different PA ladders.…”
Section: Introductionmentioning
confidence: 81%
“…This qualitative conjecture is confirmed by calculations for X + = H + , CH 3 + . Let us consider the protonation of a model system, where two vicinal CH bonds are bent toward each other, mimicking a small fused ring . Angles ε of 110° and 94° simulate five- and four-membered carbocycles, respectively, thereby representing two characteristic MN systems.…”
Section: The Protonation Of Neutral Molecules – Basicitymentioning
confidence: 99%
“…For instance, we have conclusively shown that the PA values reproduce well the selectivity in the electrophilic reactions of benzene fused to small strained rings (Mills-Nixon effect), in good accordance with numerous experimental findings. [19][20][21] We shall show in the forthcoming discussion that the proton affinity is closely related to the orientational properties of various substituents, attached to the We commence discussion with the methyl substituent. It is useful to give PA increments of toluene for the sake of comparison; they are 6.3, 3.0 and 7.4 kcal mol À1 for ortho, meta and para protonation, respectively, 11 and represent a close similarity with the corresponding values in a-methylnaphthalene and for the C(1) and C(3) positions in b-methylnaphthalene (Table 2).…”
mentioning
confidence: 99%